Sistem Informasi Pemakaian Sparepart Mesin Packing pada PT. XYZ - Triana Elizabeth; Stephanie Darmawan H (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2015)
One of the products produced by PT XYZ is instant noodles. The production process in producing instant noodles takes place in several stages, including passing the packing stage. Therefore, it takes some packing machine which can expedite the process of packaging of instant noodles, so the quality can be maintained. To maintain the smooth process of packing, then the machines must be kept in good condition and unfit for use. To be able to operate properly, it must be noted inventory of spare parts. If there is damage to a particular part of the packing machine, packing machine spare parts so it can be replaced. Due to the number of spare parts that are less clear packing machine, will interfere with the course of the process of packing and noodle production process so that it will cause harm. Therefore it needs to make a desktop-based computerized system that can provide information on the use of spare parts packing machine also can provide information on the number of spare parts that tersedia.Sistem This information is built with VB.Net programming language and IDE program using Microsoft Visual Studio 2008 and Microsoft SQL DBMS server 2008.